Queimas controladas in situ em áreas de eucalipto : uso de retardantes e comportamento do fogo - Lima, Daiane Cristina de (2019)
Forest fires generate several losses in native and forestry. An efficient method of fire mitigation is the use of fire retardants, however, the use of some of these products present problems related to environmental toxicity, high prices and lack of recommendations for practical use. The efficiency of fire retardants in the area of Eucalyptus urograndis (E. grandis x E. urophylla clone H13) at the age of six years, considering different volumes of syrup and concentrations retardants were evaluated. Three retardants were tested: two commercials (Phos-Chek® and Hold Fire®) and one alternative classified as a hydroretent polymer (Nutrigel®), with five concentrations each (as recommended by manufacturers). The fire behavior was evaluated through of the variables of the fire line propagation velocity, flame length and their respective reduction rates, remaining post-burning fuel material and fuel material consumed in response to the effect of the retarders with water, only water and without application (control). The increase of the in syrup volume all the retardants allowed a greater efficiency in relation to the reduction of the fire behavior, and the volume of syrup of 2 L m-2 in the use of the retardants was recommended. However, the ideal Phos-chek concentration was 1%, Hold Fire 1.5% and Nutrigel 0.0060%. Nutrigel presented better adjustments in the polynomial model, indicating the ideal concentration to be applied. The evaluated retardants were efficient in the reduction of the fire behavior variables (fire line propagation velocity and flame length), following the recommendations of use in E. urograndis area.